Stage door [videorecording (DVD)] - Hepburn, Katharine, 1907-2003; Rogers, Ginger, 1911-1995; Menjou, Adolphe, 1890-1963; Ball, Lucille, 1911-1989; Arden, Eve, 1908-1990; Miller, Ann, 1923-2004; Ferber, Edna, 1887-1968 (Archive collection., 2016)
"Stars galore shine in this nominee for 4 Academy Awards including best picture. A fast, witty story of aspiring actresses living at a theatrical boarding house. Based on an Edna Ferber/George S. Kaufman play, the tale was considerably rewritten for film, so much that Kaufman quipped it should be called Screen Door. What matters most to an acting hopeful is an open door. With humor and heart, this excellent movie suggests some things that matter more" --Container.